Chemical composition and microbial evaluation of Argentinean Corrientes cheese - Vasek, Olga M. (2008)
The chemical and microbial composition of an artisanal cheese made from raw cow's milk produced and consumed in the province of Corrientes (north-eastern Argentina) was evaluated using standard methods. Corrientes cheese has high moisture content (50-60%), normal protein and fat contents (21-27 and 22-26% respectively), and is low in salt (0.5-2.0% w/w). Microbial counts also varied significantly between samples (colony-forming units per gram ranges covering logs of 5-11), probably due to environmental contamination in the raw material. These results will help produce higher quality Corrientes cheeses with well-defined characteristics.